A model to understand type I oxidations of biomolecules photosensitized by pterins - Lorente, Carolina (2021)
Photosensitized oxidations, in part responsible for the harmful effect of UV and visible radiation on biological systems, can take place through type I (generation of radicals) and type II (singlet oxygen) mechanisms. Pterins are heterocyclic compounds, widespread in living systems and involved in relevant biological functions. Pterins present a profuse and amazing photochemistry and are endogenous photosensitizers that act mainly via type I mechanism. This survey is aimed to contribute to a better understanding on the complex set of competitive pathways involved in type I photosensitization. Based on studies performed in model systems with pterins as photosensitizers, this review explores the mechanisms involved in the type I photooxidations of proteins, DNA and lipids sensitized by pterins. The generation of radicals and their subsequent reactions are described together with the analysis of the role of O2 and reactive oxygen species. The chemical modification of pterins seeking for better properties and the effect of the photochemical processes at a cellular level are also analyzed.